2021
DOI: 10.3390/genes12020282
|View full text |Cite
|
Sign up to set email alerts
|

Prevalent ALMS1 Pathogenic Variants in Spanish Alström Patients

Abstract: Alström syndrome (ALMS) is an ultrarare disease with an estimated prevalence lower than 1 in 1,000,000. It is associated with disease-causing mutations in the Alström syndrome 1 (ALMS1) gene, which codifies for a structural protein of the basal body and centrosomes. The symptomatology involves nystagmus, type 2 diabetes mellitus (T2D), obesity, dilated cardiomyopathy (DCM), neurodegenerative disorders and multiorgan fibrosis. We refined the clinical and genetic diagnosis data of 12 patients from 11 families, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
(47 reference statements)
2
3
0
Order By: Relevance
“…Consistent with previous reports ( Marshall et al, 2005 ; Marshall et al, 2007a ; Marshall et al, 2007b ; Marshall et al, 2015 ; Ozantürk et al, 2015 ; Bea-Mascato et al, 2021 ), most of the variants (85%, 28/33) detected in the current cohort were clustered in exons 8, 10, and 16, further confirming these three exons as ALMS1 variant hot spots. The exons 8,10 and 16 are the three largest exons of the ALMS1 gene, containing 6.1 kilobases (kb), 1.9 kb and 1.2kb, respectively.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Consistent with previous reports ( Marshall et al, 2005 ; Marshall et al, 2007a ; Marshall et al, 2007b ; Marshall et al, 2015 ; Ozantürk et al, 2015 ; Bea-Mascato et al, 2021 ), most of the variants (85%, 28/33) detected in the current cohort were clustered in exons 8, 10, and 16, further confirming these three exons as ALMS1 variant hot spots. The exons 8,10 and 16 are the three largest exons of the ALMS1 gene, containing 6.1 kilobases (kb), 1.9 kb and 1.2kb, respectively.…”
Section: Discussionsupporting
confidence: 93%
“…All the patients in this study suffered from ocular symptoms, while the systemic manifestations in our cohort were highly variable. The frequencies of other systemic symptoms were comparable to those reported in previous studies, except for DCM ( Marshall et al, 2005 ; Marshall et al, 2007a ; Marshall et al, 2007b ; Marshall et al, 2015 ; Ozantürk et al, 2015 ; Bea-Mascato et al, 2021 ), which was not observed in our cohort of patients. In one previously reported Chinese cohort that included 21 patients, DCM was observed in 17% of the patients ( Rethanavelu et al, 2020 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations